How to regulate the acute physiological response to "aeobic" high-intensity interval exercise - Tschakert, G.; Kroepfl, J.; Mueller, A.; Moser, O.; Groeschl, W.; Hofmann, P. (Journal of Sports Science & Medicine, 2015)
The acute physiological processes during "aerobic" high-intensity interval exercise (HIIE) and their regulation are inadequately studied. The main goal of this study was to investigate the acute metabolic and cardiorespiratory response to long and short HIIE compared to continuous exercise (CE) as well as its regulation and predictability. Six healthy well-trained sport students (5 males, 1 female; age: 25.7 ± 3.1 years; height: 1.80 ± 0.04 m; weight: 76.7 ± 6.4 kg; VO2max: 4.33 ± 0.7 l·min-1) performed a maxi-mal incremental exercise test (IET) and subsequently three different exercise sessions matched for mean load (Pmean) and exercise duration (28 min): 1) long HIIE with submaximal peak workloads (Ppeak = power output at 95 % of maximum heart rate), peak workload durations (tpeak) of 4 min, and recovery durations (trec) of 3 min, 2) short HIIE with Ppeak according to the maximum power output (Pmax) from IET, tpeak of 20 s, and individually calculated trec (26.7 ± 13.4 s), and 3) CE with a target workload (Ptar-get) equating to Pmean of HIIE. In short HIIE, mean lactate (Lamean) (5.22 ± 1.41 mmol·l-1), peak La (7.14 ± 2.48 mmol·l-1), and peak heart rate (HRpeak) (181.00 ± 6.66 b·min-1) were significantly lower compared to long HIIE (Lamean: 9.83 ± 2.78 mmol·l-1; Lapeak: 12.37 ± 4.17 mmol·l-1, HRpeak: 187.67 ± 5.72 b·min-1). No significant differences in any parameters were found between short HIIE and CE despite considerably higher peak workloads in short HIIE. The acute metabolic and peak cardiorespir-atory demand during "aerobic" short HIIE was signifi-cantly lower compared to long HIIE and regulable via Pmean. Consequently, short HIIE allows a consciously aimed triggering of specific and desired or required acute physiological responses.